MinION nanopore sequencing of an influenza genome - Wang, Jing; Moore, Nicole E.; Deng, Yi-Mo; Eccles, David A.; Hall, Richard J. (Frontiers in Microbiology, 2015)
Influenza epidemics and pandemics have significant impacts on economies, morbidity and mortality worldwide. The ability to rapidly, and accurately, sequence influenza viruses is instrumental in the prevention and mitigation of influenza. All eight influenza genes from an influenza A viruses were amplified simultaneously and then subjected to sequencing on a MinION nanopore sequencer. A complete influenza virus genome was obtained that shared greater than 99% identity with sequence data obtained from the Illumina Miseq and traditional Sanger-sequencing. The laboratory infrastructure and computing resources used to perform this experiment on the MinION nanopore sequencer would be available in most molecular laboratories around the world. Using this system, the concept of portability, and thus sequencing influenza viruses in the clinic or field is now tenable.